Alternation and Reposition in Arabic Stylistics: A Conceptual Reappraisal and Its Application to the Arabic Poetry - Achmad Khusnul Khitam; Zahrotus Sa'idah (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This article revisits the concepts of alteration and reposition from the perspective of contemporary stylistics. Rather than treating them solely as grammatical deviations, the study conceptualizes both phenomena as strategic linguistic choices that enrich meaning, foreground particular semantic elements, and shape poetic expression. Drawing upon classical Arabic rhetorical scholarship and modern stylistic theory, the article proposes a comprehensive framework for understanding alternation and reposition as stylistic mechanisms operating across lexical, syntactic, and semantic levels. To demonstrate the analytical applicability of this framework, selected poems by Mahmud Sami al-Barudi are examined qualitatively. The analysis shows that alternation and reposition are not merely ornamental rhetorical devices but constitute deliberate stylistic strategies through which the poet intensifies emotional expression, expands semantic possibilities, creates textual cohesion, and directs readers' interpretive attention. These findings contribute to bridging the gap between classical Arabic rhetoric and contemporary stylistic analysis while offering a more comprehensive approach to the linguistic study of Arabic literary texts.